Dental and medical advertising: comparative analysis of the rules of professional conduct - Luciana Vigorito MAGALHÃES; Tamara Soledad Frontanilla RECALDE; Marcos Vinícius COLTRI; Hermes de Freitas BARBOSA; Marco Aurelio GUIMARÃES; Ricardo Henrique Alves da SILVA (Faculdade São Leopoldo Mandic, 2018)
In health care professional activities, advertising is an issue that raises serious discussions and is the cause of some ethical suits in professional entities, since every advertising should follow the provisions of the Code of Professional Responsibility. Therefore, this research study aimed at analyzing, comparing and discussing articles related to advertising and marketing, considering the current regulations from dental and medical entities. In Dentistry, this subject is ruled by the Code of Professional Conduct, Chapter XVI, 'From advertising and marketing'. In Medicine, information is found in two regulations and in several chapters of the Code of Medical Ethics and in Resolution No. 1.974/2011 of the Federal Council of Medicine, which establishes the guiding criteria for medical advertising. The three regulations present articles that refers to participation in mass media, required information in advertisements, use of sensationalism and self-promotion, and publishing of unproven specialties and titles, highlighting the importance of these topics. The medical regulation also includes participation in publishing ads of manufacturing companies and an exclusive committee to deal with advertising and marketing issues, topics that are not considered in the dental regulation.